Koszty uzyskania regionalnej pomocy publicznej w specjalnych strefach ekonomicznych - Sztando, Andrzej (Allowable Expenses of the Public Regional Aid within the Borders of Special Economic Zones, 2008)
The article focuses on the sphere of costs that an economic subject investing in the special economic zone has to bear in order to gain the right to obtain the national public aid, so-called regional aid. In the initial sections of the article, the author presents the special economic zone as a tool of regional policy of a country. In the further sections, particular costs, from the above mentioned, are discussed in detail, indicating the ones that the costs are incurred in relation to, in what cases the costs are borne and how high they mount to. The presentations are enriched with the examples being the result of conducted research and direct interviews. The final section of the article includes the information about the controversial issues as far as some of the described costs and their relation to the efficiency of the regional policy. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 461-469